Driving forces and mitigating strategies of CO2 emissions in China: A decomposition analysis based on 38 industrial sub-sectors. (15th April 2022) - Wen, Hong-xing; Chen, Zhe; Yang, Qian; Liu, Jin-yi; Nie, Pu-yan
Abstract: Due to the substantial industry heterogeneity in China, CO2 emissions and the major forces driving these emissions may vary in different sub-sectors. However, this topic has rarely been discussed at the industrial sub-sector level. To fill this gap, using an generalized Divisia index model (GDIM) incorporating investment factors, and considering 38 industrial sub-sectors, this study investigated the trajectories of China's industrial CO2 emissions and their driving forces, both at the overall industrial sector and its sub-sector levels. The results showed, (1) during 2000–2017, 97.2% of the increases in China's total industrial CO2 emissions was attributable to four sub-sectors. (2) Investment scale was the largest driver of increases in CO2 emissions, followed by output scale and energy consumption. (3) Carbon intensity of investment, energy intensity, and investment efficiency were main drivers of reductions in CO2 emissions, but their effects remained limited. (4) The roles of different drivers varied across sub-sectors, resulting in great heterogeneity in emission trajectories between different sub-sectors. The findings indicate the necessity of designing emission-reduction strategies at the sub-sector level, and more efforts should focus on the electricity, heat, metallurgy, mining, and chemical industries. Highlights: 97.2% of the changes in CO2 emissions was attributable to four sub-sectors. Emission-promotion effect of investment scale exceeded that of output scale. Emission-reduction effect of energy intensity was less than the expected. Strategies to mitigate CO2 emissions should be designed at the sub-sector level. Efforts to reduce CO2 emissions should focus more on PSESW, SPFM, NPM, and RCMC.